Path analysis and empirical test of medical service enhancement for common prosperity under government participation - Chen, Baoqi; Zhang, Xigang (Frontiers in Public Health, 2023)
The level of medical services is the link between the two strategic goals of "healthy China" and "common prosperity", and government participation plays an important adjustment role in it, so it is of great theoretical and practical significance to study its inner logic. In this paper, we firstly analyze the mechanism of medical service level to promote the development of common prosperity and the role of government in it; secondly, we construct a panel dynamic regression model and a threshold regression model to verify the relationship between the three. It is found that the contribution of both equity and efficiency of health care services to the achievement of common wealth is non-linear, and the degree of government participation plays an important adjustment role, with single and double threshold effects between them and the level of common prosperity, respectively. In the process of participating in the medical service market, the government should clearly position itself, actively play the demand-led role of the market, encourage private capital to provide quality medical services, and purposefully optimize the financial expenditure structure according to the local actual situation.